Stone Age and Early Metal Period Archaeology and Settlement Patterns in the Lake Pyhäjärvi Micro-Region, Karelian Isthmus, Russia - Seitsonen, Oula; Nordqvist, Kerkko; Gerasimov, Dmitriy V. (The Finnish Antiquarian Society, 2016)
Recent Finnish-Russian research cooperation on the Karelian Isthmus, north-west Russia, has completely changed views on the area’s prehistory. In this paper we describe the methodology and results of archaeological field surveys and test excavations carried out in the so-called Lake Pyhäjärvi micro-region in 2005–2008. In the course of the project’s field studies, the number of Stone Age and Early Metal Period sites in the area increased tenfold, and the exceptional, well-stratified settlement site of Kunnianniemi with nearly three-metredeep archaeological deposits was located. Recent studies provide reference material for the recently studied nearby areas and a working framework for further inquiries related to, for instance, the spatio-temporal changes in the settlement pattern, material culture, subsistence base, socio-cultural structure, and contact networks.